(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The application of new methodological approachеs in using morphometric methods and allocation of morphostructure of the Earth Crust sedimentary layer on Northern folded zone of Armenia and its geological interpretation are considered.